An Online Educational Platform for New Media Art in Thailand - Javanalikhikara, Haisang; Phaosavasdi, Kamol (Journal of Urban Culture Research, 2019)
In the global art scene New Media Art has become part of artistic practice since the 1950s. Global-ly it has been presented, accounted for, and widely applied. How-ever in Thailand, education about New Media Art has been limited. There was no hub where either artists or the public could learn about New Media Art genre. This research article will discuss the methods and production of an online New Media Art instructional platform supporting an increased awareness and understanding to Thai artists and society. This online platform will take the form as a multimedia e-magazine emphasizing the immediate relationship between itself (online com-munication) and the subject matter (New Media Art).